2017
DOI: 10.1126/scisignal.aan8355
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and ST2 mediate FAK-dependent antitumor immune evasion through transcriptional networks

Abstract: Focal adhesion kinase (FAK) mediates tumor cell–intrinsic behaviors that promote tumor growth and metastasis. We previously showed that FAK also induces the expression of inflammatory genes that inhibit antitumor immunity in the microenvironment. Here, we identified a crucial, previously unknown role for the dual-function cytokine IL-33 in FAK-dependent immune evasion. In murine squamous cell carcinoma (SCC) cells, specifically nuclear FAK enhanced the expression of the genes encoding IL-33, the chemokine CCL5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 44 publications
4
88
0
Order By: Relevance
“…[28][29][30] Here, we reported that IL-33 was upregulated in ESCC tissue sections, suggesting that IL-33 overexpression might be correlated with ESCC progress. Our results were confirmed by a recent study in murine squamous cell carcinoma cells, 19 indicating that IL-33 has a significant function in ESCC progression. In addition, functional analysis observed that IL-33 was significantly related with invasive depth, degree of differentiation, and TNM stage and a poorer survival rate.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[28][29][30] Here, we reported that IL-33 was upregulated in ESCC tissue sections, suggesting that IL-33 overexpression might be correlated with ESCC progress. Our results were confirmed by a recent study in murine squamous cell carcinoma cells, 19 indicating that IL-33 has a significant function in ESCC progression. In addition, functional analysis observed that IL-33 was significantly related with invasive depth, degree of differentiation, and TNM stage and a poorer survival rate.…”
Section: Discussionsupporting
confidence: 90%
“…17,18 A previous study found that IL-33 is restrictively expressed in murine squamous cell carcinoma cells, and it could activate FAK downstream to regulate CCL5 expression and tumor growth. 19 In this study, we aimed to examine the expression and function of IL-33 in ESCC and the underlying mechanism both in vitro and in vivo. Furthermore, the corresponding effect of IL-33 in regulating cell proliferation, cell cycle, migration, invasion, and clonogenicity were also explored.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysates were prepared for immunoblotting and immunoprecipitation as previously described (3,7).…”
Section: Immunoprecipitation and Immunoblot Analysismentioning
confidence: 99%
“…Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase that is frequently over-expressed in cancer, where it functions downstream of integrins and growth factor receptors to regulate a diverse range of cellular functions, including survival, proliferation, adhesion, migration, angiogenesis, stemness, and more recently, cytokine expression (1,2). FAK plays a pivotal role in transducing signals from the plasma membrane and the nucleus (2)(3)(4)(5)(6)(7)(8). It is recognized as a high-value druggable target for cancer therapy, resulting in the development of multiple FAK kinase inhibitors that are being tested in clinical trials (reviewed in Lee et al, (1)).…”
Section: Introductionmentioning
confidence: 99%